Effects of Warmed Fluid Irrigation Intervention and Forced-Air Warming Intervention on Hypothermia in Transurethral Operation Under Spinal Anesthesia (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to investigate an effective nursing intervention for prevention of hypothermia and thermal discomfort in patients undergoing transurethral procedure under spinal anesthesia.Method/Statistical Analysis: A total of 63 patients were randomly assigned to one of 3 groups. During the procedure, the warmed fluid irrigation group received warm irrigation fluid at 37°C, while the forced-air warming group received forced-air warming by means of Bair Hugger set at 38°C. The control group received room-temperature irrigation fluid.Findings: Body temperature measured immediately after the procedure showed a significantly higher in the warmed fluid irrigation group than in the control group. The level of thermal discomfort on arrival at the recovery room was significantly lower for the warmed fluid irrigation group than for the other two groups.Improvements/Applications: The present results suggest that warmed fluid irrigation is more effective than forced-air warming for preventing hypothermia and thermal discomfort during a transurethral procedure under spinal anesthesia.